Educational conditions of Muslim majority countries in comparison to the leading nations - Zubair Zafar Khan (Penerbit Universiti Kebangsaan Malaysia, 2013)
Background:Muslims are the Second largest Religious group after Christians in the World and ruling on around fifty one Countries and own more than 80% Oil Reserves of the World. But in respect of Educational progress they are far behind from their neighboring Countries. Objectives: This essay seeks to highlight the Educational conditions of Muslim Majority Countries in the World at present. Findings: The conditions of Muslims are worse than one can expect without observing the data presented in this Article. For Instance, 51 Muslim Majority Countries collectively have 2313 Universities, while USA alone have 2138 Universities, Brazil 1844, Philippines have 1321 Universities etc. Discussion: An attempt has been made in this essay to analyze the representation of Muslim Majority Countries in the field of education in comparison to some leading nations of the World in the light of latest data available.